Empowering Digital Literacy for Underprivileged Youth in Jakarta - Sinta Novanana (PT FORMOSA CENDEKIA GLOBAL, 2022)
The research entitled the digital literacy empowerment model for underprivileged youths uses qualitative methods. Researchers use a descriptive type of research to describe the facts, conditions, motivations of the youth in their digital literacy skills. The aim of the research is to provide the most suitable empowerment model for underprivileged youths in Jakarta area. The study was conducted on 52 youths in the Jakarta area, namely the Marunda Rusunawa, Palmerah and Bidaracina areas. This study tries to measure the digital literacy framework, which includes digital skills, digital safety, digital ethics, and digital culture. The study was carried out during the Covid 19 pandemic thus empowering is delivered under strict Covid 19 protocols. The empowering of Digital literation become very important.